Pembentukan Identitas Penggemar Melalui Media Baru (Studi Pada Remaja Penggemar Boyband K-Pop 2PM) - Citra Nuranisa (Universitas Al Azhar Indonesia, 2015)
Nowadays, hallyu or Korean Wave is becoming a phenomenon in various coun tries including Indonesia. Indonesia is one of the country which became a target to spread one of Hallyu Wave Product which is KPop. KPop itself is a Korean popular music which including various genre of music such as pop, rock, jazz, R&B, hip hop, and reggae. The presence of KPop in Indonesia through media is also a form of music globalization through media which can form someone’s new identity. This research tries to find out how fans’ identity formation through new media. This research used a descriptive qualitative method with in depth interview. This re search used globalization and media, popular culture, fans and popular culture, and self identity formation by Stone (1982). Informants in this research chosen with purposive sam ple, they are adolescent KPop fans from 1922 years old. After doing this research, concluded that new media and intensity of its use contrib utes in forming users’ identity in media use aspect. Intensity of media using that used by informants could make them found many information and alternatives related to identity as K-Pop and 2PM fans. After being a fan of K-Pop, informants also formed their new identities that also change their life style which seen from their appearance, consumption behavior, and informants’ conversation topic.